Comparison of proliferation and differentiation of calvarial osteoblast cultures derived from Msx2 deficient and wild type mice - Urlić, Inga (Array, 2009)
Abstract: We analyzed proliferation and differentiation of calvarial osteoblasts derived from Msx2 deficient in comparison with wild type mice. Calvarial osteoblast cultures from five to eight days old Msx2 deficient, heterozygous and wild type mice were studied for difference in proliferation and differentiation. Proliferation rate was assessed by counting cell number, BrdU and Calcein AM labeling. Differentiation was assessed by Von Kossa and alkaline phosphatase staining, northern blot hybridization with bone differentiation markers, infection of cell cultures with retrovirus expressing GFP under the control of type I collagen promoter fragment. At day six, cell number in cell culture derived from Msx2 deficient mice was 20% lower then in culture from wild type mice. There were 16.8% BrdU labeled cells in cell culture from Msx2 deficient mice, 20.9% in culture from heterozygous mice and 21.6% in culture from wild type mice. Cell cultures from Msx2 deficient mice showed lower intensity of fluorescence when marked with Calcein AM then cultures from wild type mice. Von Kossa staining showed increased mineralization and northern blot analysis showed increased levels of bone differentiation markers in cell cultures derived from Msx2 deficient mice. GFP came on earlier in Msx2 deficient cultures after infection with Col2.3 GFP retrovirus. We conclude that calvarial osteoblasts derived from Msx2 deficient mice have a lower rate of proliferation and demonstrate increased osteoblastic differentiation when compared to osteoblasts derived from wild type mice